Seasonal Changes in Fe along a Glaciated Greenlandic Fjord - Hopwood, Mark J.; Connelly, Douglas P.; Arendt, Kristine E.; Juul-Pedersen, Thomas; Stinchcombe, Mark C.; Meire, Lorenz; Esposito, Mario; Krishna, Ram (Frontiers in Earth Science, 2016)
Greenland’s ice sheet is the second largest on Earth, and is under threat from a warming Arctic climate. An increase in freshwater discharge from Greenland has the potential to strongly influence the composition of adjacent water masses with the largest impact on marine ecosystems likely to be found within the glaciated fjords. Here we demonstrate that physical and chemical estuarine processes within a large Greenlandic fjord are critical factors in determining the fate of meltwater derived nutrients and particles, especially for non-conservative elements such as Fe. Concentrations of Fe and macronutrients in surface waters along Godthåbsfjord, a southwest Greenlandic fjord with freshwater input from 6 glaciers, changed markedly between the onset and peak of the meltwater season due to the development of a thin (<10 m), outflowing, low-salinity surface layer. Dissolved (<0.2 µm) Fe concentrations in meltwater entering Godthåbsfjord (200 nM), in freshly melted glacial ice (mean 38 nM) and in surface waters close to a land terminating glacial system (80 nM) all indicated high Fe inputs into the fjord in summer. Total dissolvable (unfiltered at pH <2.0) Fe was similarly high with concentrations always in excess of 100 nM throughout the fjord and reaching up to 5.0 µM close to glacial outflows in summer. Yet, despite the large seasonal freshwater influx into the fjord, Fe concentrations near the fjord mouth in the out-flowing surface layer were similar in summer to those measured before the meltwater season. Furthermore, turbidity profiles indicated that sub-glacial particulate Fe inputs may not actually mix into the outflowing surface layer of this fjord. Emphasis has previously been placed on the possibility of increased Fe export from Greenland as meltwater fluxes increase. Here we suggest that in-fjord processes may be effective at removing Fe from surface waters before it can be exported to coastal seas.